PENGARUH PENGGUNAAN SISTEM E-FILING, E-BILLING, DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Lucia Esameralda; Tri Ciptaningsih; Mochamad Arif Budiarto (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to analyze the effect of implementing e-Filing, e-Billing, and knowledge of taxation on taxpayer compliance. The population in this study is individual taxpayers in the city of Banjar. Sampling was carried out using the purposive sampling method, the sampling criteria were taxpayers who had an NPWP in Banjar City, submitted SPT using the e-Filing system, and paid taxes using e-Billing. The samples obtained in this study were 110 respondents. Methods of data collection using primary data. Data was collected using a questionnaire through Google Forms. The data analysis technique used in this research is the multiple regression analysis techniques. The results of this study indicate that the application of e-Filing and knowledge of taxation has a positive and significant effect on taxpayer compliance while the implementation of the e-Billing system shows no effect on taxpayer compliance.